2004
DOI: 10.1111/j.0105-1873.2004.0424d.x
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to patch testing patients with para‐phenylenediamine allergy secondary to temporary black henna tattoos

Abstract: The objective of this work was to carry out a clinicopathological study to ascertain whether clinical and histopathologic differences existed between oral lichen planus OLP patients with and without metal restorations. The predominant clinical form in both groups was reticular white, with no statisically significant differences between the forms associated or not with metal. The histological variables showed no statistically significant differences between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 3 publications
0
29
1
5
Order By: Relevance
“…The high dose induced a statistically significant increase in the incidence of hepatic neoplasia in male rats and it induced a significant dose-related positive trend in the incidence of liver neoplasms in both sexes [22]. p-Phenylenediamine, added to sample 7, was reported to induce allergy [23,24]; it also caused dermal toxicity and pathomorphological lesions in guinea-pigs [25]. A recent study revealed that p-phenylenediamine induced DNA damage in SV-40 immortalized human uroepithelial cells [26] and p53-mediated apoptosis in Mardin-Darby canine kidney cells [27].…”
Section: Toxicity Studymentioning
confidence: 99%
“…The high dose induced a statistically significant increase in the incidence of hepatic neoplasia in male rats and it induced a significant dose-related positive trend in the incidence of liver neoplasms in both sexes [22]. p-Phenylenediamine, added to sample 7, was reported to induce allergy [23,24]; it also caused dermal toxicity and pathomorphological lesions in guinea-pigs [25]. A recent study revealed that p-phenylenediamine induced DNA damage in SV-40 immortalized human uroepithelial cells [26] and p53-mediated apoptosis in Mardin-Darby canine kidney cells [27].…”
Section: Toxicity Studymentioning
confidence: 99%
“…Temporary tattoos made with henna, especially black henna, have also been reported to contain PPD, causing allergic contact dermatitis [3,4,7]. In our case it is possible that the previous use of black henna tattoos, common in the Moroccan culture, was the initial sensitisation for the development of the described allergic contact dermatitis since the dermatitis already occurred 12 h after the dying procedure [2]. Diagnosis can be made through patch testing including PPD in the standard set, although in such cases the test concentrations should be lowered to 0.01% in order to avoid severe reactions [2,4].…”
mentioning
confidence: 74%
“…In our case it is possible that the previous use of black henna tattoos, common in the Moroccan culture, was the initial sensitisation for the development of the described allergic contact dermatitis since the dermatitis already occurred 12 h after the dying procedure [2]. Diagnosis can be made through patch testing including PPD in the standard set, although in such cases the test concentrations should be lowered to 0.01% in order to avoid severe reactions [2,4]. It would also be useful to include a test for textile dyes as they frequently also cross react with PPD, so that patients can avoid these in the future.…”
mentioning
confidence: 83%
“…Therefore, patch testing with PPD is recommended to be performed in a step-wise procedure starting with a low concentration of 0.01 % PPD in petrolatum. If the concentration of 0.01 % PPD has not elicited any allergic skin reaction at the first reading, a new patch test chamber with a stronger concentration can be applied of 0.1 or 1.0 % PPD in petrolatum [57]. This titration of PPD dose ensures that children with a high reactivity to PPD are diagnosed with the lowest possible dose of PPD for the shortest duration of time.…”
Section: Diagnosismentioning
confidence: 99%